Ekofeminisme Pemberdayaan Perempuan Dalam Pengolahan Sampah Rumah Tangga Berbasis Psikologi (Studi Kasus Komunitas Astagina Klaten) - Riyani, WindaIka; Sari, Ramadhanita Mustika (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Gender issues related to the central role of housewives in waste management have a great influence on the handling and management of waste in households. This study uses a qualitative descriptive method by holistically examining the ecofeminism movement of the Astagina community. Women, who are seen as the largest producers of household waste, have a big role in overcoming community problems. The existence of social movements that care for the environment such as the women's ecofeminism movement not only saves nature, but also proves the equal role between women and men in protecting the ecosystem. Pro-environmental behavior in every decision-making from the cognition of protecting the environment is the motive for the emergence of self-efficacy in Astagina women to recycle household waste. The ecofeminism movement carried out by the Astagina women's community also provides awareness and knowledge to Klaten women so as to provide motivation and psychological encouragement to care for the environment by recycling waste through recycling which becomes useful goods